Оценка эффективности систем контроля и наблюдения за объектами с радиационными материалами - Лисиченко, Г.В.; Забулонов, Ю.Л.; Буртняк, В.М. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2010)
Is examined the task of the optimization of automated checking structure and track system for objects with radiation materials. The criterion of structure optimality is offered.